THE PROBLEM OF INTEGRATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN SYSTEM OF VOCATIONAL TRAINING OF THE FUTURE TEACHER OF MUSIC - Nataliіa М. Popovych (Information technologies and learning tools, 2013)
In the article there are analyzed specificity and problems of integration of information and communication technologies into the system of  teacher of music vocational training in different level pedagogical education. Ways of realization of possibilities of modern technologies of information influence to educational process are revealed. The basic pedagogical tasks of use of information and communication technologies are defined. It is proposed the systematic approach to the ICT integration into the educational process aiming to increase the subject learning efficiency. There are considered conditions of effective functioning of information and communication technologies in educational process.